Further Comment: "Cross-Sectional Differences Among Commercial Banks" - Saunders, Robert J. (Journal of Financial and Quantitative Analysis, 1974)
Marion L. Chiattello [1] has provided additional empirical support for the suggestion that, because of the high degree of linear interdependence between many of the variables commonly used in banking regression studies, it may be necessary to interpret explanatory variables in a cross-sectional regression equation, not as representing individual influences, but as representing more general factors. Further, he has provided more empirical support for the suggestion that principal component analysis might be useful in helping to isolate and identify some of these general factors.